Perspective of Women in Neurosurgery: Quantitative Study Interpreting Journey of Professional Identity Formation in Female Doctors of Low Middle Income Country: Neurosurgery: Professional Identity in Female Doctors of Low Middle Income Country - Kamboh, Usman Ahmad; Saleem, Ammara; Amin, Gulrez; Noor, Ayesha; Kushef, Hooria; Manzoor, Mahwish; Anwar, Malik Adeel (Pakistan Journal of Health Sciences, 2025)
Globally, there is a shift towards choosing medical and allied specialities over neurosurgery. In Pakistan, where female medical students now outnumber males, this trend has led to a significant gap in the availability of qualified neurosurgeons. Objectives: To assess how the perception of neurosurgery evolves from final year medical school to house job among female doctors focusing on educational adequacy, socioeconomic factors and challenging career choices. Methods: This cross-sectional descriptive study was conducted through a validated questionnaire. This questionnaire encompassed demographic information, and a series of items designed to evaluate students’ educational perceptions regarding neurosurgery, their socioeconomic viewpoints on neurosurgery, and their perspectives on neurosurgery training within Pakistan. Results: We received 216 responses from participants, with 115 (53.2%) being final-year students and 101 (46.8%) serving as house officers. 57.9% of participants disagreed to consider neurosurgery as a career option whereas 97.7% considered neurosurgical illnesses challenging and interesting. Neurosurgery involving long operating hours was the strongly agreed question among participants (97.2%). Final-year students were significantly more likely to perceive their neurosurgery education as inadequate (61.7%). Likewise, they reported greater concerns about limited job opportunities compared to house officers (20% vs 7.9%, p=0.012). Conclusions: It was concluded that although there is considerable interest in neurosurgery, enrollment among females remains low due to educational gaps, socioeconomic barriers and gender challenges. Limited teaching resources, the demanding nature of the field, and perceived negative impacts on personal life among female doctors contribute to this trend.